Analisa Sistem Operasi Real-Time pada Pengendalian Robot Industri: Evaluasi Performa dan Stabilitas - Viona Veliza; Rangga Saputra (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
In the modern industrial world, robots like mechanical arms in automotive factories or packaging lines must move quickly and safely. For this, a real-time operating sistem (RTOS) is needed—think of it as a